Intravenous Acetaminophen Effect on Postoperative Narcotic Analgesic Demand after Elective Cesarean Section - Mahshid Ghasemi; Maryam Vosoughian; Mastaneh Dahi-Taleghani; Mehrnaz Sohrabi; Seyed Amir Mohajerani (Novelty in Biomedicine, 2016)
Background: Opioid analgesics are the mainstay of the treatment of postoperative pain. Appropriate monitoring of patients receiving opioid analgesics is essential to detect those with side effects such as respiratory depression. The discovery of Acetaminophen as a COX-3 variant may represent a primary central mechanism by which acetaminophen decrease pain. The aim of this study was to assess the effect of intravenous acetaminophen on morphine requirement in post-operation pain after elective cesarean section. Materials and Methods: In a randomized clinical trial, patients’ candidate for elective cesarean section. In experiment group, intravenous acetaminophen (1000 mg/6 hour) was administered and normal saline to control group. Visual analogue scale (VAS) was measured at 1, 3, 6, 12, and 24 hours post-operation. Besides, Morphine dose requirement were measured during next 24 hours. Results: 83 patients were enrolled in the study; which 44 patients assigned in placebo group and 39 in Acetaminophen. Mean Age of placebo group was 29.64±5.55 and Acetaminophen was 30.33±5.50 which was not significantly different (p=0.568). Only at 1 and 3 hours, there was a significant difference between two groups of study. Total dose of morphine requirement was 5.73±2.78 mg/24 h in placebo group and 3.64±2.42 in Acetaminophen group which was significantly different (p=0.001). Conclusion: Intravenous Acetaminophen could decrease post cesarean pain and decrease post operation total morphine requirement particularly at first 3 hours post operation.